Spectroscopic Studies of Quality of Commercial Polyethylene Terephthalate Storage Containers - Gunasekaran, S.; R., Hemamalini (Asian Journal of Chemistry, 2016)
FTIR spectral measurements have been made to differentiate the commercial polyethylene terephthalate (PET) containers with the source polyethylene terephthalate (PET). The internal standards are ratios indicative of the quality of the sample. The internal standards are computed for certain specific modes of vibration and are compared to identify the quality and purity of the samples. The purity of the commercial PET containers has been confIrmed by UV-Visible spectroscopy. Further, microwave measurements have been made on all the commercial and source samples to study their dielectric behaviour in K and X bands using microwave bench equipped with Gunn and Klystron oscillators respectively and guided with rectangular waveguide. A suitable correlation between dielectric constant and their infrared spectra has been achieved.